Evaluation of the cardiopulmonary and antinociceptive effects of bupivacaine administered epidurally at the first lumbar vertebra in awake dogs - Silva, P. E.S. [UNESP] (2016)
The aim of this study was to evaluate the effect of epidural bupivacaine administration at the first lumbar vertebra on cardiopulmonary variables, arterial blood gases and anti-nociception. Sixteen healthy female dogs were randomly assigned into two groups based on bupivacaine dose: G1 group, 1mg kg-1 or G2 group, 2mg kg-1, diluted in the same final volume (1mL4kg-1). Cardiopulmonary variables were measured and arterial blood gas was collected (T0), it was repeated 10 minutes after intravenous administration of butorphanol 0.4mg kg -1 (T1). Anesthesia was induced with intravenous etomidate at 2mg kg-1 and the epidural catheter was introduced and placed at the first lumbar vertebra. Thirty minutes later, bupivacaine was administered epidurally. Cardiopulmonary measurements and arterial blood gas analysis were recorded at 10 minute intervals (T2 to T6). Evaluation of pre surgical anti-nociception was performed at 5 minute intervals for 30 minutes by clamping the hind limbs, anus, vulva, and tail with the dogs awake. Subsequently, ovariohysterectomy was performed and adequacy of surgical anti-nociception was evaluated at 5 time points. Parametric data were analyzed using the F test with a <0.05 significance. After bupivacaine administration, there were differences between groups just for bicarbonate means (HCO3 -) on T6 (P=0.0198), with 18.7±1.3 and 20.4±0.8 for G1 and G2, respectively. After T1, before bupivacaine administration, both groups presented a slightly lower pH, base excess (BE), the end-tidal carbon dioxide tension (PECO2), and partial pressure of carbon dioxide (PaCO2), suggesting mild metabolic acidosis. G2 showed better antinociceptive effect both before and during surgery. It was possible to perform ovariohysterectomy in 87.5% of the G2 bitches and 25% of the G1 bitches. The two doses of bupivacaine evaluated do not cause important alterations in the studied parameters and the dose of 2mg kg-1 results in a better antinociceptive effect.